2019
DOI: 10.1111/cobi.13366
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing compassionate conservation

Abstract: Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 64 publications
(117 reference statements)
0
87
1
Order By: Relevance
“…The concept of the Quality Adjusted Life Year (QALY) is used in many countries to assess the benefit to human well-being and life expectancy against demands on a limited budget [40]. However, as Hayward et al [6] pointed out, trade-offs such as these are not compatible with the extreme version of Compassionate Conservation advocated by Wallach et al Oomen et al drew attention to the potential for substantial costs to humans resulting from an extreme perspective on the moral salience of non-human sentience [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of the Quality Adjusted Life Year (QALY) is used in many countries to assess the benefit to human well-being and life expectancy against demands on a limited budget [40]. However, as Hayward et al [6] pointed out, trade-offs such as these are not compatible with the extreme version of Compassionate Conservation advocated by Wallach et al Oomen et al drew attention to the potential for substantial costs to humans resulting from an extreme perspective on the moral salience of non-human sentience [31].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that lethal control can plausibly lead to a net positive effect on individual wellbeing compared with taking no action. Similarly, Russell et al [26], Driscoll and Watson [27] and Hayward et al [6] pointed to lose-lose outcomes for welfare and conservation where lethal control of invasive species is eschewed. Gough island in the South Atlantic is a good example: nearly two million sea-bird chicks are currently predated annually by non-native invasive mice introduced by people, driving some endemic species to the brink of extinction [28].…”
Section: Risks Of Perverse Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their interpretation of virtue ethics leads them to argue that it is always wrong to kill sentient vertebrates in the interests of conservation . This perspective has been challenged by Oommen et al () and by Hayward et al (), who argue it places too much emphasis on individuals over collectives (populations or species) and may also lead to poor outcomes for both welfare and conservation.…”
Section: Lion Trophy Huntingmentioning
confidence: 99%
“…This control is ultimately based on a preference for ‘natural’ processes, and the definition of native is largely cultural (Macdonald et al, ). Some conservationists argue that conservation is premised on nativism, and that native species are of more value to their ecosystems than are non‐native species (discussed in Hayward et al, ). Without further qualification, this is probably over‐stating this case.…”
Section: Pheasant Shootingmentioning
confidence: 99%